Detoxification and discoloration of Moroccan olive mill wastewater by electrocoagulation - Hanafi, F.; Assobhei, O.; Mountadar, M. (Journal of hazardous materials, 2010)
The objective of the present study was to assess the electrocoagulation treatment of olive mill wastewater using an aluminum electrode. We have examined the effect of the following parameters on the removal of chemical oxygen demand (COD), polyphenols and dark color removal efficiency: Electrolysis time, Current density, Chloride concentration and Initial pH. The olive mill wastewater (OMW) – diluted 5 times – used in this study had 20.000 mg/L chemical oxygen demand, 3.6 mS/cm conductivity and acidic pH (4.2). It also contains considerable quantities of polyphenols (260 mg/L). The evolution of the physico-chemical parameters during the treatment by electrocoagulation showed that under the following conditions: electrolysis time 15 min, NaCl concentration 2 g/L, initial pH 4.2 and current density 250 A/m 2, the discoloration of the olive mill wastewater, the reduction of the chemical oxygen demand and the reduction of polyphenols exceeded 70%, the electrodes consumption was 0.085 kg Al/kg COD removed and the specific energy consumed was 2.63 kWh/kg COD removed. Under these optimal experimental conditions, olive mill wastewater became non-toxic for Bacillus cereus.